Optimization of City Library and Archives Services Yogyakarta Through Literacy Introduction Tour Program at the Library City Yogyakarta - Priatna, Yolan; Fitri Ani, Hawa (Universitas Terbuka, 2025)
This article discusses efforts to optimize services at the Yogyakarta City Library through the Literacy Introduction Tour program at the Yogyakarta City Library (TALITA). The research method used is qualitative which is analyzed using descriptive analysis techniques. Data collection was carried out by interviewing 3 (three) informants who were divided into key, main and additional informants as well as a study of various relevant literature. The results of the study indicate that the TALITA program is effective in increasing public interest and understanding of literacy. The implication of this study is the importance of developing innovative programs in expanding access and increasing community involvement in the world of literacy, especially through the use of library services. It is hoped that this study can provide a positive contribution to the development of library and literacy services in the city of Yogyakarta and become a reference for other regions in efforts to improve public literacy.